David J. Burn (ed.), The Book of Requiems: From the Earliest Ages to the Present Period, 1450–1550, (Leuven: Leuven University Press, 2022). ISBN 978-9462703261, 208 pp, €70 (hardback). - Marx, Wolfgang (Journal of the Society for Musicology in Ireland, 2023)
A review of David J. Burn (ed.), The Book of Requiems: From the Earliest Ages to the Present Period, 1450–1550, (Leuven: Leuven University Press, 2022). ISBN 978-9462703261, 208 pp, €70 (hardback).